2021
DOI: 10.3390/ijerph18147554
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Imaging as a Visual Biofeedback Tool in Rehabilitation: An Updated Systematic Review

Abstract: Rehabilitative ultrasound imaging (RUSI) is used by physical therapists as a feedback tool for measuring changes in muscle morphology during therapeutic interventions such as motor control exercises (MCE). However, a structured overview of its efficacy is lacking. We aimed to systematically review the efficacy of RUSI for improving MCE programs compared with no feedback and other feedback methods. MEDLINE, PubMed, SCOPUS and Web of Science databases were searched for studies evaluating efficacy data of RUSI to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
(124 reference statements)
0
19
0
Order By: Relevance
“…The use of ultrasound imaging (US) is currently increasing among physiotherapists as is a portable, safe, accessible and low-cost (in comparison with other imaging methods) tool for a wide variety of purposes [ 1 ]. Currently, physiotherapists access US equipment for guiding invasive procedures in order to ensure the patients’ safety [ 2 ], as a visual feedback tool for guiding motor control exercises [ 3 ] and as an instrument for evaluating and monitoring musculoskeletal structures [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of ultrasound imaging (US) is currently increasing among physiotherapists as is a portable, safe, accessible and low-cost (in comparison with other imaging methods) tool for a wide variety of purposes [ 1 ]. Currently, physiotherapists access US equipment for guiding invasive procedures in order to ensure the patients’ safety [ 2 ], as a visual feedback tool for guiding motor control exercises [ 3 ] and as an instrument for evaluating and monitoring musculoskeletal structures [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it would be relevant in future studies to analyze possible differences between biofeedback modalities such as ultrasound imaging, pressure biofeedback units, and electromyography. In previous research, it has been observed that different types of feedback can generate different effects depending on the protocol applied and the type of injury [57], which could enrich the knowledge developed around the recovery processes and the use of biofeedback applied in the type of injury considered in this article.…”
Section: Discussionmentioning
confidence: 91%
“…In addition to these advantages, clinicians currently demand biosensors with acceptable utility (i.e., reliability, specificity, sensitivity, and validity) as a complement or alternative to manual explorations [ 31 , 32 ]. Since recent developments in US technology allow the measurement of multiple objective metrics by using Doppler (for detecting and analyzing flows) [ 33 ], M-mode (for real-time feedback during muscle contractions or for measuring thickness changes) [ 34 ], or elastography (for measuring stiffness metrics) [ 35 ], along with the assessment of large structures that previously could not be entirely visualized in a single image (i.e., panoramic US) [ 36 ], this tool is one of the most attractive alternatives to these imaging methods to meet these demands.…”
Section: Introductionmentioning
confidence: 99%